The Effect of Family Prosperity by Matthew 18:20 on The Growth of The Loss of GKA Agape - Surabaya Congregation - Ani Teguh Purwanto (Theological Journal Kerugma, 2019)
This study aims to examine the effect of family altar according to Matthew 18:20 on the spiritual growth of the GKA Agape Surabaya congregation. The reason for this research is due to the low growth of the faith of the congregation due to lack of time to fellowship with God. The sample of this study was 91 people of GKA Agape Surabaya, who were obtained through simple random sampling. The results showed that: 1). there is an influence between the organization of the family altar with the spiritual growth of the church (r = 0.337; R square = 0.114; p = .000) ; 2). the contribution independent of the variable implementation of the family altar the dependent variable of the church's spiritual growth was 11.4%. This research implies that when holding a family altar has a positive influence on the growth of the congregation, a congregation that has a good and regular family altar is expected to have good spiritual growth as well.